A Phase I Trial to Determine the Safety and Tolerability of Autophagy Inhibition Using Chloroquine or Hydroxychloroquine in Combination With Carboplatin and Gemcitabine in Patients With Advanced Solid Tumors - Karim, Nagla Abdel; Ullah, Asad; Ahmad, Imran; Bahassi, Elmustapha; Olowokure, Olugbenga; Khaled, Ahmed; Davis, Harold; Morris, John C. (Frontiers in Oncology, 2022)
Background. Autophagy is a catabolic process triggered in cells during periods of metabolic or hypoxic stress to enable their survival that may also impart advantages to tumors. Inhibition of early-stage autophagy can rescue cancer cells, while inhibition of late-stage autophagy leads to cell death due to accumulation of damaged organelles. Chloroquine (CQ) and hydroxychloroquine (HCQ) inhibit late phase autophagy. We assessed the safety, tolerability and activity of combining CQ/HCQ with carboplatin and gemcitabine (CG) in patients with advanced solid tumors. Methods. This single institution phase 1 dose-escalation study was designed to evaluate the maximum tolerated dose (MTD) of CQ/HCQ, in combination with CG in patients with advanced solid tumors. Secondary objectives were to determine ORR, PFS and OS. A starting dose of CQ/HCQ 50 mg was used in conjunction with CG and increased in increments of 50 mg in each dose cohort. Grade 3 or greater toxicity that is treatment-related, and was not self-limited, or controlled in less than 7 days was considered dose limiting toxicity (DLT). Results. Twenty-two patients were enrolled. All patients had at least one prior treatment, and 11 of them had 3 prior regimens. HCQ 100 mg daily was found to be the MTD in combination with CG with thrombocytopenia and/or neutropenia dose-limiting. Median OS was 11 months, and the 1- and 3- year overall survivals were 30% and 7%, respectively. Median progression free survival was 5 months and the 6-, 12-, and 18-month progression-free survivals were 48%, 21% and 14%, respectively. Conclusions. The MTD identified for CQ/HCQ was lower than previously reported with concomitant use of chemotherapeutic regimes likely due to the myelosuppressive nature of CG.